Effect of mechanical scarification on seed germination of Rosa baitagensis Kamelin & Gubanov - Ulziibayar, Uyanzul; Uuganbaatar, Khishigsuren; Gurbazar, Byamba-Yondon; Dalaikhuu, Usukhjargal (Mongolian Journal of Botany, 2024)
As a result of climate change and land degradation, the quality of seeds and resources of natural plants is decreasing year by year, and their distribution area is shrinking. Seed germination is one of the important stages in the life cycle of plants, and the development of methods and technologies to increase the intensity of germination is crucial for the protection of plant diversity and genetic resources. Baitag rose (Rosa baitagensis Kamelin & Gubanov), a native plant of our country, grows in a limited area in the Dzungar Gobi District. We aimed to test the effect of physical factors, or mechanical damage, on increasing the seed germination of this species. After 14 days of incubation in sterile WPM (woody plant medium), the species showed an increase in germination percentage compared to the control, but it was not statistically significant (p=0.698). We continued the experiment, and after 28 days of incubation in the medium, when the seeds were damaged, germination increased threefold, and the intensity of germination was statistically significant (p<0.05). Effects of air pollution on ascorbic acid content in the leaves of some woody plants Хураангуй. Уур амьсгалын өөрчлөлт, газрын доройтлоос үүдэлтэйгээр хөрсний үржил шим муудаж, хур тунадас багасаж байгаа зэрэг шалтгааны улмаас байгалийн ургамлын үрийн чанар, нөөц жил ирэх тусам багасаж байгаа төдийгүй тархац нутаг нь хумигдаж байна. Үрийн соёололт бол ургамлын амьдралын эргэлтийн нэг чухал үе шат бөгөөд түүний соёололтын эрчмийг нэмэгдүүлэх арга, технологийг бий болгох нь ургамлын олон янз байдал, генетик нөөцийг хамгаалах асуудалд маш чухал юм. Манай орны унаган ургамал Байтаг сарнай (Rosa baitagensis Kamelin & Gubanov) нь ургамал газарзүйн Зүүнгарын говийн тойрогт тодорхой хязгаарлагдмал цэгт тархан ургадаг. Бид уг зүйл ургамлын үрийн соёололтыг нэмэгдүүлэхэд физикийн хүчин зүйл буюу механик сорвижуулалтын нөлөөг үзэхийг зорьсон. Энэхүү зорилгынхоо хүрээнд уг зүйл сарнайн үрийг ариутган WPM (woody plant medium) орчинд 14 хоног өсгөвөрлөсний дараа гэмтээж үргэлжлүүлэн өсгөвөрлөн хяналтын хувилбартай харьцуулахад соёололтын хувь нэмэгдсэн хэдий ч статистикийн хувьд ялгаагүй байв (p=0.698) статистикийн хувьд ялгаагүй байв. Бид туршилтыг үргэлжлүүлэн 14 болон 28 хоног тэжээлт орчинд өсгөвөрлөсний дараа үрийг гэмтээхэд соёололт 3 дахин нэмэгдэж, соёололтын эрчим нь статистикийн хувьд ялгаатай байв (p<0.05). Түлхүүр үг: Байтаг сарнай, механик гэмтэл WPM